The Effect Of Quantum Teaching Model In Science Learning On Student’s Learning Motivation Of 4TH Grade Student - Khilda Tazkiah Tunnufus; Widya Karmila Sari Ahmad; Rohana Rohana (Program Studi PGSD FIP UNM, 2023)
This research was conducted on the basis of the discovery of problems found at SDN Borong, namely the low motivation for student learning. The purpose of this study is to determine the description of the application of the quantum teaching model in science learning, (2) to find out the picture of student learning motivation, and (3) to determine the influence of the application of the quantum teaching model on science learning on the learning motivation of grade IV UPT SPF students at SDN Borong. This research uses a quantitative approach with a type of experimental research in the form of quasi-experimental design type non-equivalent control group design. The study population is all grade IV. The samples in the study were class IV students who were selected by purposive sampling technique. Research data were collected using observations, questionnaires, and documentation provided before and after the implementation of learning. The data were analyzed using descriptive and inferential analysis. The results of the descriptive analysis showed that the first treatment went well and the second treatment went very well . The results of inferential analysis using independent sample t-test showed the difference in post non-test results between the experimental class and the control class. This shows that there is an increase in student learning motivation in the experimental group higher than the control class. So that it can be concluded that: (1) the learning process with the application of the quantum teaching model is effective, (2) the results of the student questionnaire show an increase in student learning motivation in science learning, (3) there is a significant influence on the application of the quantum teaching model on student learning motivation in science learning grade IV UPT SPF SDN Borong Kota Makassar.